2020
DOI: 10.1021/acs.jnatprod.0c00745
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium Residual Quadrupolar Couplings: Crossing the Current Frontiers in the Relative Configuration Analysis of Natural Products

Abstract: Determination of the 3D structure (configuration and preferred conformation) of complex natural and synthetic organic molecules is a long-standing but still challenging task for chemists, with various implications in pharmaceutical sciences whether or not these substances have specific bioactivities. NMR in aligning media, either lyotropic liquid crystals (LLC) or polymer gels, in combination with molecular modelling is a unique framework to solve complex structural problems whose analytical wealth lies in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 86 publications
0
46
1
Order By: Relevance
“…In case of artemisinin, the smallest Q-factor was below 0.02, with a very small of RD average below 4%. 177 with permission This result has been obtained with the stereoisomer of absolute configuration 1S, 4R, 5S, 6R, 7S, 10R, and 11R, namely, the known absolute configuration. These results have therefore demonstrated that the 3D structure/ relative configuration of complex bioactive molecules could be unambiguously determined using 2 H-RQCs, being in this case at 2 H natural abundance.…”
Section: Determination Of the Relative Configuration In Bioactive Polystereogenic Compoundsmentioning
confidence: 96%
See 1 more Smart Citation
“…In case of artemisinin, the smallest Q-factor was below 0.02, with a very small of RD average below 4%. 177 with permission This result has been obtained with the stereoisomer of absolute configuration 1S, 4R, 5S, 6R, 7S, 10R, and 11R, namely, the known absolute configuration. These results have therefore demonstrated that the 3D structure/ relative configuration of complex bioactive molecules could be unambiguously determined using 2 H-RQCs, being in this case at 2 H natural abundance.…”
Section: Determination Of the Relative Configuration In Bioactive Polystereogenic Compoundsmentioning
confidence: 96%
“…of 2 H-RQCs extracted from ANAD NMR 2D spectra, assuming that the sensitivity is nowadays a real drawback. 177 The performance of this last tool has been examined for two multicyclic chiral, natural compounds of pharmaceutical interest oriented in PBLG-based oriented samples: the strychnine, a poison, and artemisinin, an antimalarial drug used against Plasmodium falciparum malaria, as examples. Figure 37 shows the ANAD Q-resolved Fz 2D spectrum of artemisinin recorded within 15 h with only (50 mg [MW = 282.3], i.e., a molar concentration for each monodeuterated isotopomer of about 35 μmolÁL À1 ) where unambiguous 15 (over 16) 2 H-QDs can be experimentally measured and used.…”
Section: Determination Of the Relative Configuration In Bioactive Pol...mentioning
confidence: 99%
“…So far, the recent exploitation of 2 H-RQCs has been performed using the MSpin-RQC program, 51,52 a variant of MSpin, initially able to manage RDCs or RCSAs as input data. 30,53 In this work, another computational approach delivering orientational data 5) including their atomic numbering; the red and blue colors are used for identifying them.…”
Section: Data Analysis By Conarch +mentioning
confidence: 99%
“…63 Another possibility could be to explore all possible combinations of signs for each inequivalent site, using a screening-protocol computational approach. 52 Currently, the experimental approach used in this work consists in exploiting additional 13 C data ( 1 T CH ) extracted from the analysis of simple proton-coupled 1D experiments (inverse gate/single pulse) with the help of heteronuclear ( 1 T CH /2)-or ( 1 T CH /4)-resolved heteronuclear 2D spectra (see Fig. S7 and S8, ESI †).…”
Section: Analysis Of Methylene Groupsmentioning
confidence: 99%
“…NMR in weakly aligned media has become a firmly established tool for structural elucidation of organic compounds. [1][2][3] Although most applications to structural elucidation problems involved the use of residual dipolar couplings (RDCs), [4,5] mostly one-bond proton-carbon 1 D CH ones, residual chemical shift anisotropies (RCSAs), [6,7] and even 2 H residual quadrupolar couplings (RQCs) [8] have come recently into play.…”
Section: Introductionmentioning
confidence: 99%